Product Realization A Comprehensive Approach - Tomovic, Mileta; Wang, Shaoping (Springer US : Imprint: Springer, 2009)
Product Realization: A Comprehensive Approach is based on selected papers presented at the International Conference on Comprehensive Product Realization 2007 (ICCPR2007). The extended papers will provide the opportunity for scholars from all around the world to discuss their academic programs, identify research opportunities, and initiate joint research programs in the area of comprehensive product realization. Engineering design has evolved from an isolated semi-empirical activity to a highly interconnected, multidisciplinary product realization collaborative process. Written by experts in the field of engineering design, Product Realization: A Comprehensive Approach is a must have book for engineering professionals interested in the latest developments in product life cycle management. Covering such topics as: Product life cycle and assessment parameters Measuring the impact of product lifecycle management Social issues of product lifecycle management Product design optimization Product lifecycle Management and the virtualization of product information About the Editors: Mileta M. Tomovic is the W.C. Furnas Professor of Enterprise Excellence in the Department of Mechanical Engineering Technology at Purdue University. His research interests are in the area of system dynamics and controls, manufacturing processes, design optimization, collaborative design, product lifecycle management, modeling of rapid prototyping and fast free form fabrication methods, and web-based multi-user platform development for industrial tooling customer-supplier resource management. Shaoping Wang is a Professor of Mechatronics and Dean of Mechatronics at the School of Automation Science and Electrical Engineering at Beijing University of Aeronautics and Astronautics.